Curie Temperature and Optical Damage Resistance of Hf:Ce:Fe:LiNbO3 Crystals with Different Hf Concentrations - TAN Chao; DAI Li; HAN Xian-bo; SHAO Yu (Journal of Harbin University of Science and Technology)
A series of Hf:Ce:Fe:LiNbO3 crystal with variousHf4+(2,4,6,8mol%) ion concentration were grown by Czochralski method In order to study the effect of different doping concentration of Hf4+ ion on curie temperature and optical damage resistibility of Hf:Ce:Fe:LiNbO3 crystal Differential thermal analysis curve of Hf:Ce:Fe:LiNbO3 crystal was measured by differential thermal analyzers, and the curie temperature change of the crystal was analyzed The optical damage resistance of the crystal was measured by the facula distortion methodThe experimental results show that the Curie temperature increased by 20℃ and reaches the maximum of 1224℃ when the doping concentration of Hf4+ ions was 4mol% As the concentration of Hf4+ ions in the crystal increases, the optical damage resistanceability increases The optical damage resistance ability of the Hf(8mol%):Ce:Fe:LiNbO3  crystal is two orders of magnitude than Hf(2mol%):Ce:Fe:LiNbO3